Transmission of parental neuroticism to offspring's depression: The mediating role of rumination. (2nd September 2014) - Sachs‐Ericsson, Natalie; Selby, Edward A.; Hames, Jennifer L.; Joiner, Thomas E.; Fingerman, Karen L.; Zarit, Steven H.; Birditt, Kira S.; Hilt, Lori M.
Abstract Rumination is a cognitive process that involves repetitively focusing on the causes, situational factors and consequences of one's negative emotion, and it is a potent risk factor for depression. Parental depression and neuroticism may exert an influence on offspring's development of rumination, which may increase offspring's risk for depression. The current study included 375 biological parent–offspring dyads. Parents were assessed for depressive symptoms and neuroticism; adult offspring were assessed for depressive symptoms and rumination. Structural equation modelling was used to examine the effects of parental depressive symptoms and parental neuroticism on adult offspring's depression, and to determine whether offspring's rumination mediated this relationship. Results provided evidence that offspring's rumination fully mediated the relationship between parental neuroticism and offspring's depressive symptoms. Parental depressive symptoms and neuroticism may contribute a genetic predisposition for depressive symptoms in offspring, but it also may promote an environment in which maladaptive cognitive processes, such as rumination, are learned. Given the role that rumination plays in mediating the association between neuroticism and depressive symptoms—targeting rumination in the treatment of high risk individuals would be important in reducing onset of depressive disorders. Copyright © 2014 John Wiley & Sons, Ltd.